AUXIN RESPONSE FACTOR3 Regulates Floral Meristem Determinacy by Repressing Cytokinin Biosynthesis and Signaling. Issue 2 (25th January 2018) - Zhang, Ke; Wang, Ruozhong; Zi, Hailing; Li, Yongpeng; Cao, Xiuwei; Li, Dongming; Guo, Lin; Tong, Jianhua; Pan, Yanyun; Jiao, Yuling; Liu, Renyi; Xiao, Langtao; et al.
Abstract : AUXIN RESPONSE FACTOR3 integrates the activities of AGAMOUS and auxin to control cytokinin biosynthesis and signaling, thereby coordinately regulating floral meristem maintenance and termination. Abstract: Successful floral meristem (FM) determinacy is critical for subsequent reproductive development and the plant life cycle. Although the phytohormones cytokinin and auxin interact to coregulate many aspects of plant development, whether and how cytokinin and auxin function in FM determinacy remain unclear. Here, we show that in Arabidopsis thaliana, cytokinin homeostasis is critical for FM determinacy. In this developmental context, auxin promotes the expression of AUXIN RESPONSE FACTOR3 ( ARF3 ) to repress cytokinin activity. ARF3 directly represses the expression of ISOPENTENYLTRANSFERASE ( IPT ) family genes and indirectly represses LONELY GUY ( LOG ) family genes, both of which encode enzymes required for cytokinin biosynthesis. ARF3 also directly inhibits the expression of ARABIDOPSIS HISTIDINE KINASE4, a cytokinin receptor gene, resulting in reduced cytokinin activity. Consequently, ARF3 controls cell division by regulating cell cycle gene expression through cytokinin. In flowers, we show that AGAMOUS (AG) dynamically regulates the expression of ARF3 and IPT s, resulting in coordinated regulation of FM maintenance and termination through cell division. Moreover, genome-wide transcriptional profiling revealed both repressive and active roles for ARF3 in early flower development. Our findings establish a molecular link between AG and auxin/cytokinin and shed light on the mechanisms of stem cell maintenance and termination in the FM.